1984
DOI: 10.1161/01.hyp.6.5.675
|View full text |Cite
|
Sign up to set email alerts
|

Chronic angiotensin II infusion decreases renal norepinephrine overflow in conscious dogs.

Abstract: SUMMARY Sympathetic nerve activity and in particular renal sympathetic nerve activity were monitored in six conscious dogs subjected to 6 days of intravenous angiotensin (ANG II) infusion (20 ng/kg/min). This was accomplished by measurement of both arterial and renal venous plasma catecholamine concentration. During the initial 4 hours of ANG II infusion, mean arterial pressure (MAP) increased 35 ± 8 mm Hg from a control value of 101 ± 4 mm Hg. Although there were no significant changes in arterial plasma nore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 31 publications
6
49
0
Order By: Relevance
“…Cessation of the angiotensin II caused blood pressure and SNA to return to control levels. The observation of sympathoinhibition during angiotensin II infusions is supported by Carroll et al (17), who measured renal norepinephrine overflow as an indirect index of RSNA. Six days of angiotensin II hypertension was associated with marked reductions (not increases) in renal norepinephrine spillover.…”
Section: The Role Of Angiotensin In Regulating Long-term Levels Of Snamentioning
confidence: 84%
See 1 more Smart Citation
“…Cessation of the angiotensin II caused blood pressure and SNA to return to control levels. The observation of sympathoinhibition during angiotensin II infusions is supported by Carroll et al (17), who measured renal norepinephrine overflow as an indirect index of RSNA. Six days of angiotensin II hypertension was associated with marked reductions (not increases) in renal norepinephrine spillover.…”
Section: The Role Of Angiotensin In Regulating Long-term Levels Of Snamentioning
confidence: 84%
“…However, this is not without debate, as measurements of peripheral plasma catecholamine levels during angiotensin II suggest sympathetic activity does not change (17,51), whereas renal norepinephrine spillover levels suggest sympathetic activity is decreased during angiotensin II hypertension (17). In part, this may reflect a differential nature of sympathetic activation with activation of RSNA and no change to other organs.…”
Section: The Role Of Angiotensin In Regulating Long-term Levels Of Snamentioning
confidence: 99%
“…26 Moreover, norepinephrine overflow in the kidney, an index of renal sympathetic nerve activity, was not increased in Ang II-infused dogs. 27 Finally, the present finding that there was no significant difference in postsaralasin blood pressure levels between control rats (108±4 mm Hg) and Ang II-infused rats (115±6 mm Hg) but that the difference was still significantly higher in sodium chloride-supplemented Ang II rats (136±6 versus 108±4 mm Hg, /?<0.01) suggested that other factors than the direct vascular action of Ang II are less important in the maintenance of blood pressure in Ang II-treated rats as compared with sodium chloride-supplemented Ang II rats. This is compatible with the present data, which indicate that either ECFV measured by isotope dilution method or SNS activity measured by plasma norepinephrine concentration and vasodepressor response to hexamethonium were normal in Ang II-treated rats, but both indexes were significantly increased in Ang 11+NaCI rats.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of renal SNA has also been directly measured during ANG II-induced hypertension in rabbits (2) and indirectly in dogs (4), suggesting that this suppression is not a salt-dependent effect, per se, but rather a baroreceptor-mediated phenomenon. Indeed, the chronic ANG II-induced decrease in renal SNA is not observed in sinoaortic-denervated animals (17,1).…”
mentioning
confidence: 97%